Recent progress of Ni-based catalysts for methanol electrooxidation reaction in alkaline media - Liu, Chunru; Yang, Fulin; Schechter, Alex; Feng, Ligang (Advanced Sensor and Energy Materials, 2023)
Methanol as an important hydrogen-rich fuel has received increasing attention in energy storage and conversion techniques, and energy release can be realized in the methanol oxidation reaction (MOR) process. Note that highly efficient catalysts are still required to drive methanol oxidation, and the Ni-based catalysts have received intensive attention due to their facile active site generation based on the electrochemical-chemical oxidation mechanisms. In light of the significant advances made recently, herein, we reviewed the recent advances of Ni-based catalysts for methanol oxidation in the alkaline medium. The fundamental of methanol oxidation in the alkaline medium was first presented, and then the catalyst design principles including synergistic effect, electronic effect, defect construction, doping effect, as well as surface reconstruction were presented; and the advances of various Ni-based catalysts for MOR are summarized and discussed by combining with some typical examples. The problems and challenges were also concluded for the Ni-based catalyst fabrication, the performance evaluation, and their application. We believe that the summary of this review will be helpful in the design of nickel-based catalysts and understanding the catalysis mechanism of nickel-based materials in alcohol fuel electrochemical reactions. [Display omitted]